HASIL BELAJAR KOGNITIF IPA FISIKA SISWA MELALUI PENERAPAN STRATEGI BOWLING CAMPUS DI KELAS VIII6 SMPN 15 PEKANBARU - Kiki Ananya Kiki Ananya; Muhammad Nor Muhammad Nor; Syahril ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims at describe cognitive learning outcomes science of physics through the implementation strategy Bowling Campus on light subject at SMPN 15 Pekanbaru. The expected benefits of this research is for students implementation Bowling Campus strategy can improve the cognitive learning to become a better student. For teachers can be used as an alternative teaching strategies to improve the quality of science physics teaching. This research was conducted in SMP 15 Pekanbaru precisely in March 2015 until June 2015 in class VIII6 totaling 39 students. The design of the research is Pre-experimental design shapes One Shot Case study. From the research results obtained by the average value of absorption of students by 76.53% and categorized as good. Based on the average value of absorption was also found that the effectiveness of learning by applying Bowling Campus declared effective strategy. Based on 20 indicators of achievement of competencies in a given light material, 14 indicators declared complete with a percentage of 70%. It can be concluded that the application of Bowling Campus strategy can be used as an alternative in order to achieve the learning outcomes of cognitive learning better students in the classroom VIII6 SMP 15 Pekanbaru.Key Words: cognitive learning outcomes, active learning, Bowling Campus, light